When readers fail to form a coherent representation of garden-path sentences - Chromý, Jan (Quarterly journal of experimental psychology (2006), 2022)
Various studies within the Good-Enough Approach observe that people often make errors in answering comprehension questions after reading garden-path sentences such as While Anna dressed the baby played in the crib. Recently, it has been claimed that readers form a full syntactic analysis of these sentences, but they do not completely prune the original misanalysis. This article presents evidence that these findings do not hold for all garden-path sentences. The main finding of the Good-Enough Approach-that the comprehension questions targeting the initial misanalysis yield significantly higher rates of incorrect answers after garden-path sentences, in comparison with after control sentences-was replicated here in three self-paced reading experiments on Czech. However, these experiments show a similar pattern of results for other comprehension questions, such as questions targeting an analysis that is not syntactically licensed at any point of processing. These results point out that certain garden-path structures may be very hard to process and that the process of garden-path repair might not be successful at all. Based on these results and the results of previous studies, the idea of a range of difficulty levels for garden-path structures is proposed.
Keywords: Language; Comprehension; self-paced reading; lidé; Sentence processing; pochopení; čtení; Reading; jazyk (prostředek komunikace); garden-path; ambiguity; Czech; Humans